The influence of organizational culture on construction risk management among Kuantan Malaysian Construction Industry: A partial least square structural equation modeling approach - Ismayana, M.P.; Adeleke, A. Q. (International Society for Everant Publisher, 2020)
Organization culture in nowadays industry especially the construction industry has become something crucial in determining the success of the construction project. The unsuitable culture can have an impact on the organization itself, based on the project management perspective. As for the construction, it is likely to face a different problem such as the quality that did not meet the expectation, overbudget, delay in terms of scheduling, unsafe condition and dissatisfaction of the clients. These problems above show how risky the construction project is. There are a few characteristics that show that the construction industry is different from other industries. This is why understanding the organizational culture is crucial because of the differences that will be faced. To address these issues above, this study aims 1) to investigate the relationship between market culture and Management risk in Pahang Malaysia; and 2) to identify the relationship between the hierarchy culture and Management risk in Pahang Malaysia. The researcher collected data from 89 respondents among construction companies in Kuantan. In this research, the PLS-SEM technique was used to analyze both the measurement and structural models. The result shows that there is a significant positive relationship between market culture and Management risk among the construction industry in Pahang, Malaysia. Meanwhile, the relationship between hierarchy culture and management risk was statistically not significant. Implications for practice and future research were also discussed.